Sawtooth control with modulated ICRH in JET-ILW H-mode plasmas. (22nd October 2020) - Lerche, E.; Lennholm, M.; Carvalho, I.S.; Jacquet, P.; Mantsinen, M.; Dumortier, P.; Van Eester, D.; Graves, J.P.; Card, P.; Noble, C.
Abstract: Sawtooth pacing with modulated ion-cyclotron resonance heating (ICRH) has been demonstrated to be very efficient in JET-ILW L-mode plasmas (Lerche et al 2017 Nucl. Fusion 57 036027, Lennholm et al 2017 Fusion Eng. Des. 123 535–40), where the main heat source in the plasma centre is provided by the RF accelerated minority ions. In H-mode plasmas with substantial neutral beam injection power, this technique is more challenging since the fast beam particles have a stabilizing effect on the sawteeth, making it more difficult to trigger a sawtooth crash by removing the additional fast particle sources induced by ICRH inside the q = 1 surface. New results from JET-ILW experiments, showing that this technique can also be used in high power H-modes with considerable success will be presented, with focus on the sawtooth triggering efficiency at different pacing frequencies and plasma parameters, both during the flat-top phase of the discharges and during the H-mode exit and plasma termination.